Analysis of Factors that Influence the Use of Electronic Money in Indonesia - Puspa Nada Aliyah Akbar; Rima Rachmawati (GoAcademica Research & Publishing, 2023)
This empirical study scrutinizes the factors influencing electronic money usage in Indonesia, focusing on financial literacy, security, user accessibility, and government support. Employing a quantitative approach with a descriptive and verificative analysis of data from 210 potential users, the research identifies financial literacy as a cornerstone for adoption, yet finds it insufficiently developed. Security concerns are highlighted as significant, with perceived vulnerabilities in e-money systems. Accessibility challenges, due to infrastructural and educational gaps, further impede e-money's widespread use. The government's role is deemed crucial but not yet fully effective in creating a supportive ecosystem for e-money. Despite the positive influence of these factors, the research concludes that the full potential of e-money is unrealized, with the study's limitations acknowledging unexplored variables that may also affect e-money's utilization in Indonesia. These insights aim to inform strategies to address these barriers and enhance e-money adoption in the Indonesian market.